The Outlines of Meaning’s Analysis of Social Phenomena in the Concept of S. L. Frank - Matveeva, Natalya (Slavica, 2018)
The present paper deals with the problem of how cultural meanings are perceived in S. L. Frank’s social theory. His conception lies between two main paths of sociological thought: Durkheim’s cognition of social facts as objective phenomena on the one hand, and Weber’s cognition of subjective meanings of personal actions, on the other. In his theory Frank concentrates on the concept of objective forming idea-force, which resembles the concept of social fact in its quality of exerting pressure on individual consciousness and volition, but it should be brought into harmony with interpretive methodology. In Frank’s view social ideas are regarded as a force forming social relations and therefore lie in the foundation of social institutions. These are, for example, ideas of state, of family, of friendship and so on. Social ideas are connected with the consciousness of the individual by their moral force. That is why such ideas are accepted by the individual at the emotional level of his spiritual life, because they believe that these ideas are true and organize their meanings and activities according to them. Thus social meanings of moral good or evil in human relations and in the social structure arise. At the same time they signify the emergence of sacred phenomena in society. Human beings, according the Frank’s theory, have an internal need to be possessed by the sacred senses that give them the feeling of the participation in the implementation of the transcendent goals. Society is an objective living idea which provides sacred meanings for the individual. On the whole, a society’s life is formed by the historically specific complex of ideas that are freely accepted or rejected by individuals and determine their feelings and behavior. There is no contradiction between personal freedom, creativity and social structure in S. Frank’s theory. The author of the present paperfinds similarities between S.Frank’s ideas and the fundamentals of cultural sociology.